From Kitab Malay to Literary Indonesian: A Case Study in Semantic Change - Riddell, Peter G. (Studia Islamika, 2012)
This paper discusses semantic movement as evidenced in Malay/Indonesian Islamic texts. The primary text in focus provides an example of ‘Abd al-Ra’ūf al-Singkīlī’s Malay commentary on the Quran, Tarjumān al-Mustafīd, produced around 1675. The study of the lexical data from this text is informed by comparative reference to three modern Indonesian texts of Sūrah Yūsuf: Mahmoed Joenoes’ rendering (1954), the official Indonesian government rendering drawn from Al-Quraan dan Terjemahnya (1974), and H.B. Jassin’s rendering (1978). The goal of this paper will be to answer two questions. First, the semantic range of certain lexical items used in the ‘Abd al-Ra’ūf Quran commentary compare with the norms of late 20th century literary Indonesian. Second, the semantic change of differences identified in this comparative process.DOI: 10.15408/sdi.v19i2.362